Evaluation of the antioxidant and gastroprotective activity and HPLC analysis of the hydroalcoholic extract of Tocoyena formosa leaves (Cham. & Schlecht) K. Schum. (February 2018) - Alves Santana Cesário, Francisco Rafael; Rodrigues de Albuquerque, Thaís; Fernandes da Silva, Bruno Anderson; Mendes de Lacerda, Giovana; Rodrigues, Lindaiane Bezerra; Brito Pereira Bezerra Martins, Anita Oliveira; Quintans-Júnior, Lucindo Jose; Guedes da Silva Almeida, Jackson Roberto; Vale, Mariana Lima; Melo Coutinho, Henrique Douglas; Alencar de Menezes, Irwin Rose
Abstract: The peptic ulcer is a gastric disorder that affects millions of people and yet they cause many side effects. In this sense, natural products represent an important alternative to the discovery of compounds with gastroprotective activity. The present work has as its objective to evaluate the antioxidant and gastroprotective activity of the Hydroalcoholic Extract of Leaves from Tocoyena formosa (Cham. & Schlecht.) K. Schum (HELTF), this being much emphasized in traditional medicine for inflammatory morbidities and gastric symptoms. For the evaluation of the antioxidant activity, FRAP and DPPH tests were carried out, and for the evaluation of the gastroprotective activity, gastric lesion induction by ethanol, acidified ethanol, indomethacin and physical barrier tests were used. Antioxidant assay of HELTF revealed an EC50 of 558.66 μM FeSO4/g and IC50 of 189.78 μg/ml for FRAP and DPPH respectively. In gastroprotective, in ethanol model, all the doses presented significant activity in comparison to controls, however, in the gastric lesion induction test by acidified ethanol and indomethacin, only the dose of 200 mg/kg presented with significance. In the physical barrier test presented evidence that protection by the formation of a protective layer associated with mucus. Concluded, therefore, that HELTF possesses antioxidant and significate gastroprotective activity.